Cluster Analysis of Agronomic Traits in Chickpea Genotypes under Cool Upland Semi-arid Region - Sabaghnia, Naser; Shekari, Fariborz; Nouraein, Mojtaba; Janmohammadi, Mohsen (Annals of Arid Zone, 2025)
This study was conducted to evaluate the genetic diversity among 50 chickpea lines grown in a randomized complete block design with three replications. The days to flower initiation, canopy width, days to maturity, plant height, chlorophyll content, ground coverage, number of subsidiary branches, the first pod height from the ground, number of pods per plant, pod weight per plant, shuck weight per plant, plant fresh weight, number of seeds per pod, number of unfilled pods per plant, protein percent, plant dry weight, hundred seed weight and seed yield were recorded. The coefficient of variation was high for chlorophyll content, ground coverage, number of subsidiary branches, first pod height from ground, number of pods per plant, number of seeds per pods, number unfilled pods , canopy width and seed yield. The chickpea traits were grouped into three groups; Cluster-I is seed yield while Cluster-II consists of chlorophyll content, ground coverage, days to flower initiation, dry matter and hundred seed weight and the other remained traits were grouped as Cluster-III. The cutoff point divided the dendrogram of chickpea genotypes into four clusters, Cluster-A, Cluster-B, Cluster- C and Cluster-D consisted of 16, 4, 11 and 19 genotypes. Four genotypes of Cluster-B namely FLIP09-228C-S00794(30 KR)-2/, TDS-Maragheh90-90, TDS-Maragheh90-373 and TDS-Maragheh90-266 based on high mean yield, high numbers of seeds and pods per plant were identified as good candidates for commercial release and can be advised for cultivation